Patrones de dispersión intrametropolitana en México - Sobrino, Jaime (El Colegio de México A.C., 2007)
This document seeks to examine the process of demographic suburbanization and occupational decentralization in the main metropolitan areas of Mexico. To this end, it uses information on residential mobility and journeys to work, variables that are available for the sample from the 2000 population and housing census. The study focuses on eight of the 55 metropolitan zones that exist in the country and the municipality is the territorial unit used to analyze intra-metropolitan change. The questions guiding this document are: i) How scattered are Mexico’s metropolitan zones? ii) What role have migration and residential mobility played in sub-urbanization? iii) How are employment and therefore journeys to work distributed within the metropolitan zones? The answers suggest conclusions about the characteristics of the suburbanization and decentralization that have taken place, raising the question of whether the country’s metropolises fit the theoretical model of a monocentric city or whether they reflect the emergence of a polycentric city.